Differential associations of parental harshness and parental disengagement with overall cortisol output at 15 years: Implications for adolescent mental health. (19th February 2022) - Doom, Jenalee R.; Peckins, Melissa K.; Hein, Tyler C.; Dotterer, Hailey L.; Mitchell, Colter; Lopez-Duran, Nestor L.; Brooks-Gunn, Jeanne; McLanahan, Sara; Hyde, Luke W.; Abelson, James L.; Monk, Christopher S.
Abstract: Psychosocial stress in childhood and adolescence is linked to stress system dysregulation, although few studies have examined the relative impacts of parental harshness and parental disengagement. This study prospectively tested whether parental harshness and disengagement show differential associations with overall cortisol output in adolescence. Associations between overall cortisol output and adolescent mental health problems were tested concurrently. Adolescents from the Fragile Families and Child Wellbeing Study (FFCWS) provided hair samples for cortisol assay at 15 years ( N = 171). Caregivers reported on parental harshness and disengagement experiences at 1, 3, 5, 9, and 15 years, and adolescents reported at 15 years. Both parent and adolescent reported depressive and anxiety symptoms and antisocial behaviors at 15. Greater parental harshness from 1–15 years, and harshness reported at 15 years in particular, was associated with higher overall cortisol output at 15. Greater parental disengagement from 1–15 years, and disengagement at 1 year specifically, was associated with lower cortisol output. There were no significant associations between cortisol output and depressive symptoms, anxiety symptoms, or antisocial behaviors. These results suggest that the unique variances of parental harshness and disengagement may have opposing associations with cortisol output at 15 years, with unclear implications for adolescent mental health.